OPTIMIZING INVESTMENT PORTFOLIO OF DANA PENSIUN TELKOM - Savira Miftah/ 29116405, Sovi
As of nowadays, the penetration level of pension fund in Indonesia is still low, only 6.26% in 2016, as the impact of low rate of pension fund literacy (10.91%) and inclusion (4.66%) in the society. Meanwhile, the current economic and employment system in Indonesia is growing. Thus, the Government see that there are some adjustment needed in the participants’ benefit in order to improve the retiree’s welfare. In 2017, Otoritas Jasa Keuangan (OJK) release a new regulation number 5/POJK.05/2017, encouraging pension fund institution to provide other benefit to the participants, such as education fund for children, religious worship fund, healthcare fund, etc. besides the existing benefit that always been given. Dana Pensiun Telkom (Dapentel) is one of Employer Pension Fund in Indonesia that offer Defined Benefit Pension Program for PT Telkom Indonesia’s retiree. The new regulation has been a concern for Dapentel. Besides, Dapentel also have to comply with the Minister of Finance Decree No 113/PMK.05/2005 on Amendment of KMK 510/06/2002 about Funding and Solvability of Employer Pension Fund. Dapentel have a surplus of Rp 472.76 billion or 2.87% in 2016 and this surplus is used by the employer to stop paying the contribution. Dapentel have to gain more return but they cannot do anything to get additional funding. Whereas if they have to provide more benefits, more contribution will be useful. So, the most possible solution that can be given to Dapentel is by focusing on their investment portfolio. The solution in this thesis will be using Markowitz Optimization Theory and Solver Microsoft Excel add-in as the tool. To find the most optimal portfolio, efficient frontier curve, Capital Allocation Line (CAL), and Global Minimum Variance (GMV) will be analyzed. Using the historical data of the past 5 years, 2013 to 2017, the result showing that Dapentel could gain more return (12.95%) with much lower standard deviation (3.58%) compare to the past performance. The weight for the optimal portfolio is by allocating 1% in on call deposit, 14% in time deposit, 20% in corporate bond, 44% in government bond, 7% in stock, 3% in mutual fund, 10% in property, and 1% in non-public stock.